The practices of yoga for the digestive system [3rd ed.] - Shankardevananda; Saraswati, Swami Satyananda [guide] (Munger Yoga Publications Trust, 2003)
Faulty diet, tension and lack of Exercise are the chief causes of most digestive disorders.This book explains how the practices of yoga and yogic diet can be utilized to balance these factors and eliminate digestive problems.Written by Dr.Swami shankardevananda Saraswati under the guidance of Swami satyananda Saraswati, the book combines the traditional medical view with the Ayurvedic and yogic views of healthy Digestion.
2013 golden jubilee edition
Keywords: Yoga -- Therapeutic use; Digestion; Digestive organs; Gastrointestinal system -- Motility; Hygiene; Digestive system; Yoga